"Advise and Rule" or "Rule by Advising": The Changing Nature of the Advisory Jurisdiction of the Constitutional Court of Kosovo. Issue 8 (December 2020) - Korenica, Fisnik
Abstract: Constitutional courts play an essential role in authoritatively interpreting constitutions. Oftentimes they go beyond the constitutional text by inventing so-called judge-made law. Their authority to interpret the text covers not only substantive parts but also the clause authorizing their jurisdiction. Such power, namely the power to interpret the limits of their jurisdiction, is often used to intervene in the interpretation of the constitution more vigorously than explicitly authorized. One example is the invention, designation, and development of the advisory jurisdiction by the Constitutional Court of the Republic of Kosovo. On that basis, the Court has, for almost ten years of its existence, pronounced on numerous fundamental issues relating to the governing system, power maps, and entitlements on political authority. The Court developed its advisory jurisdiction in a rather unpredictable and impulsive fashion; however, it steadily revealed its willingness to engage with interpretations that sought to resolve high-stakes issues. Such braveness also had a credibility cost for the Court. The year 2018 marked a major shift in the Court's interpretation of its own jurisdiction to "advise." In the Central Election Commission case, it abandoned its previous precedent and commenced a passive, restrained attitude in engaging with the constitutional interpretation on the basis of case or controversy. This Article analyzes the Court's path and change of course in this cycle.